Examination of carbon-water nanofluid flow with thermal radiation under the effect of Marangoni convection. Issue 7 (2nd October 2017) - Mohyud-Din, Syed Tauseef; Usman, Muhammad; Afaq, Kamran; Hamid, Muhammad; Wang, Wei
Abstract : Purpose: The purpose of this study is to analyze the effects of carbon nanotubes (CNTs) in the Marangoni convection boundary layer viscous fluid flow. The analysis and formulation for both types of CNTs, namely, single-walled (SWCNTs) and multi-walled (MWCNTs), are described. The influence of thermal radiation effect assumed in the form of energy expression. Design/methodology/approach: Appropriate transformations reduced the partial differential systems to a set of nonlinear ordinary differential equations (ODEs). The obtained nonlinear ODE set is solved via the least squares method. A detailed comparison between outcomes obtained by the least squares method, RK-4 and already published work is available. Findings: Nusselt number was analyzed and found to be more effective for nanoparticle volume fraction and larger radiation parameters. Additionally, the error and convergence analysis for the least squares method was presented to show the efficiency of the said algorithm. Originality/value: The results reveal that velocity is a decreasing function of suction for both CNTs. While enhancing the nanoparticle volume fraction, an increase for both thermal boundary layer thickness and temperature was attained. The radiation parameter has an increasing function as temperature. Velocity behavior is the same for nanoparticle volume fraction and suction. It was observed that velocity is less in SWCNTs as compared to MWCNTs.